(untitled) (La U Investiga, 2018)
Pregnancy despite being a physiological condition, when it happens in adolescence becomes a problem for the fetus, the family, the community and the pregnant woman itself, with its consequences in the psychological, physical and social development of the mother. of the consequent problem for health services. The information that is detailed in the present work is carried out in the Hospital San Vicente de Paul de Ibarra, in the service of Obstetric Center, with adolescent patients who enter the institution with diverse symptoms and pathologies, having as a result the number of adolescent patients admitted and treated in the area, the medical diagnoses and complications that may arise during their stay, which are manifested by their age and obstetric risk, whose data serve as a basis to obtain the results of the present investigation. The group object of the present study are adolescents between the ages of 12 to 18 years, in January to December of 2017, are patients who come to be attended in the Obstetric Center, derived from the services of Emergency and gynecology hospitalization without distinction of pathology presented at the time of entry.